Rational Water and Nitrogen Management Improves Root Growth, Increases Yield and Maintains Water Use Efficiency of Cotton under Mulch Drip Irrigation - Zhang, Hongzhi; Khan, Aziz; Tan, Daniel K. Y.; Luo, Honghai (Frontiers in Plant Science, 2017)
There is a need to optimize water-nitrogen (N) application to increase seed cotton yield and water use efficiency of field grown cotton under mulch drip irrigation system. This study evaluated the effect of the four water regimes (moderate drip irrigation from the third-leaf to the boll-opening stage (W1), deficit drip irrigation from the third-leaf to the flowering stage and sufficient drip irrigation thereafter (W2), pre-sowing and moderate drip irrigation from third-leaf to the boll-opening stage (W3), pre-sowing and deficit drip irrigation from the third-leaf to the flowering stage and sufficient drip irrigation thereafter (W4). Two N dressing ratios (7:3 (N1), 2:8 (N2) under N rate of 520 kg ha-1) on morphological and physiological traits of roots, cotton yield and water use efficiency and analyzed the relationship between root distribution and dry matter. Investigations have shown a strong correlation between root activity and water consumption in the 40-120 cm soil layer. The W3 and especially W4 treatments significantly increased root length density (RLD), root volume density (RVD), root mass density (RMD), and root activity in the 40-120 cm soil layers. RLD, RVD, RMD and root activity in the 0-40 cm soil layers at 70 days after planting (DAP) were 13.1%, 13.3%, 20.8% and 10.8% lower in N2 relative to N1, respectively. However, root activity in the 40-120 cm soil layers at 140 DAP was 31.6% higher in N2 than that in N1. Total RMD, RLD and root activity in the 40-120 cm soil profile were significantly and positively correlated with shoot dry weight. RLD and root activity in the 40-120 cm soil layer was highest in W4N2 treatments. Therefore increased water consumption in the deep soil layers resulted in increased shoot dry weight, seed cotton yield and water use efficiency. Our data will help in the future research planning of water-N management for optimal cotton yield and high water use efficiency.